Relationship between Vitamin-D Receptor Gene Polymorphism FokI and Fetuin- A as A marker of Vascular Calcification in Egyptian Hemodialysis Patients - Fatma Ibrahim Mayah (Al-Azhar University, Faculty of Medicine (Damietta), 2021)
Background: Vascular calcification is a common complication in end-stage renal disease patients and the leading cause of morbidity and mortality. Aim of the work: The current work aimed to evaluate the possible relationship between vitamin D receptor gene polymorphism FokI with fetuin-A and intact parathormone hormone in Egyptian hemodialysis patients. Patient and Methods: This study is a cross-sectional study including 50 hemodialysis patients attending the hemodialysis unit in Al-Zahra University Hospital and 30 apparently healthy persons as a control group. For all studied subjects, a detailed history was taken, physical examination, carotid intima-media thickness by carotid duplex, echocardiography, Laboratory investigations included serum levels of calcium, phosphorus, iPTH, fetuin, and genotype frequency by PCR Results: There was a highly significant increase in carotid intimal media thickness in the patient group Vs. control group & a highly significant decrease in serum Fetuin-A in the patient's group Vs. control group. There was a significant difference in the genotype distribution of FokI polymorphism among patients and control. There were significant negative relationships between FF genotype and iPTH and a highly significant negative correlation between serum fetuin-A and iPTH in the patient group. Conclusion: Vitamin D receptor gene FokI polymorphism FF genotyping is more frequent in hemodialysis patients who have higher iPTH and lower fetuin-A levels, which could identify the high-risk group susceptible to vascular calcification in hemodialysis patients. Further studies are needed.